Produksi Biodiesel dari Minyak Jelantah dengan Katalis Heterogen CaO dari Limbah Cangkang Telur - Suryandari, Ade Sonya; Ardiansyah, Zainur Risky; Putri, Vemmy Nurmala Andhani; Arfiansyah, Ilham; Mustain, Asalil; Dewajani, Heny; Mufid, Mufid (Fakultas Teknik, Universitas Brawijaya, 2021)
Nowadays, the substitute for biofuel diesel fuel is biodiesel. Waste cooking oil has the potential as a biodiesel feedstock due to its environmentally friendly, inexpensive, reduces household waste and does not compete with food needs. One effort that can be done is to use CaO catalyst from eggshell waste. Eggshells contain 95,28% CaCO3 which can be calcined to produce CaO. In this research, production of biodiesel is done by using waste cooking oil and CaO catalyst from eggshells with various variables to determine the best calcination conditions in the preparation of the catalyst. The eggshells were calcined at variable temperatures (600,700,800 and 900°C) during the time variables (2,3,4 and 5 hours). The operating conditions in the transesterification reaction were at 60°C for 2hours with a stirring speed of 700rpm and a mole ratio of oil and methanol of 1:12. The results obtained, the best calcination conditions in producing CaO catalysts were at a temperature of 800°C for 2 hours with 78,31% mass recovery. In addition, the transesterification reaction using the best catalyst produced 97,2% FAME with a density of 0,8549 gr/mL and a viscosity of 9,58 cSt.